Incremental dynamic analysis. - Vamvatsikos, Dimitrios (Earthquake engineering & structural dynamics.)
Incremental dynamic analysis (IDA) is a parametric analysis method that has recently emerged in several different forms to estimate more thoroughly structural performance under seismic loads. It involves subjecting a structural model to one (or more) ground motion record (s), each scaled to multiple levels of intensity, thus producing one (or more) curve (s) of response parameterized versus intensity level. To establish a common frame of reference, the fundamental concepts are analysed, a unified terminology is proposed, suitable algorithms are presented, and properties of the IDA curve are looked into for both single degree of freedom and multi degree of freedom structures. In addition, summarization techniques for multi record IDA studies and the association of the IDA study with the conventional static pushover analysis and the yield reduction R-factor are discussed. Finally, in the framework of performance based earthquake engineering, the assessment of demand and capacity is viewed through the lens of an IDA study.